Syncope during pregnancy in a patient with permanent cardiac pacemaker, due to increased pacing threshold. - Mohammad Ali Akbarzadeh; Morteza Safi; Isa Khaheshi; Negar Bahrololoumi Bafruee (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
A 22-year-old pregnant woman referred with syncope due to pacemaker malfunction. During the second trimester of pregnancy, the right ventricular (RV) lead pacing threshold increased and led to early generator depletion. We believe that this might happen due to lead micro-dislodgement or less probably effect of hormonal changes during pregnancy on electrode-myocardium interface.